2018
DOI: 10.1038/s41598-018-33568-8
|View full text |Cite
|
Sign up to set email alerts
|

Fine-tuning carbapenem resistance by reducing porin permeability of bacteria activated in the selection process of conjugation

Abstract: Antibiotic resistance is an emerging public health issue. Plasmids are one of the popular carriers to disseminate resistance genes among pathogens. However, the response of plasmid-carrying bacteria to antibiotic treatment and how these bacteria evolve to increase their resistance remain elusive. In this study, we conjugated plasmid pNDM-HK to E. coli J53 recipient cells and selected survivors using different concentrations of the broad spectrum antibiotic meropenem. After selection, transconjugants conferred … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 52 publications
0
19
0
3
Order By: Relevance
“…Kong et al (51) revealed that the Gly63Ser amino acid substitution within the N-terminal phosphorylation domain of OmpR affects the phosphorylation of OmpR by EnvZ. The OmpR mutant, after that, failed to initiate porin transcription, resulting in a change in membrane permeability and, subsequently, carbapenem resistance (51). The study further went on to show the synergistic effect of OmpR mutants and carbapenemase activity, with the transformation of OmpR mutants with a NDM-harboring plasmid resulting in a 100-fold increase in the carbapenem MIC (Table 1) (51). SDS-PAGE analysis of the outer membrane porins of OmpR mutants revealed a sharp decrease in the expression of both major porin groups (49).…”
Section: Alteration Of Membrane Permeabilitymentioning
confidence: 99%
See 3 more Smart Citations
“…Kong et al (51) revealed that the Gly63Ser amino acid substitution within the N-terminal phosphorylation domain of OmpR affects the phosphorylation of OmpR by EnvZ. The OmpR mutant, after that, failed to initiate porin transcription, resulting in a change in membrane permeability and, subsequently, carbapenem resistance (51). The study further went on to show the synergistic effect of OmpR mutants and carbapenemase activity, with the transformation of OmpR mutants with a NDM-harboring plasmid resulting in a 100-fold increase in the carbapenem MIC (Table 1) (51). SDS-PAGE analysis of the outer membrane porins of OmpR mutants revealed a sharp decrease in the expression of both major porin groups (49).…”
Section: Alteration Of Membrane Permeabilitymentioning
confidence: 99%
“…The loss of major outer membrane proteins, OmpK36 and OmpK35, is frequently observed in CRE, resulting in reduced permeability of the outer membrane due to structural changes in porin channels restricting the uptake of charged molecules through the bacterial cell wall ( Fig. 1 ) ( 3 , 49 , 51 ). These structural changes were due to mutations that either reduced the channel size of porins or modified its electrostatics ( 52 ).…”
Section: Alteration Of Membrane Permeabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…In the case of Escherichia coli certain general porins such as OmpF and PhoE act as a gateway for the diffusion of hydrophilic molecules (Achouak et al, 2001;Fernández & Hancock, 2012). In some cases the regular dosage of antibiotic pressure initiate certain mutational changes on transcription factor leading to the loss of porins expression as indicated by the development of carbapenem resistance in Escherichia coli trans conjugant (Kong et al, 2018). Carbapenem belongs to a class of β-lactam antibiotics which is also effective against disease caused by Pseudomonas aeruginosa (Hong et al, 2015).…”
Section: Loss Of Porinsmentioning
confidence: 99%